Negotiating post-apartheid boundaries and identities : an anthropological study of the creation of a Cape Town Suburb - Broadbridge, Helena Tara (Stellenbosch : Stellenbosch University, 2012)
Thesis (PhD)--University of Stellenbosch, 2001.